The Influence of Service Quality, Brand Image and Technology Usage on Customer Loyalty through Customer Satisfaction as a Mediating Variable in PT. Pos Indonesia Medan Branch - Putri Khalijah Tricahyanti Siregar; Arlina Nurbaity Lubis; Beby Karina Fawzeea (Journal of Business Management, 2026)
The delivery service industry in Indonesia is experiencing increasingly fierce competition along with the growth of e-commerce. PT Pos Indonesia as a state-owned enterprise faces challenges in maintaining customer loyalty amid the dominance of private competitors such as J&T Express and JNE. This study aims to analyze the influence of service quality, brand image, and technology usage on customer loyalty with customer satisfaction as a mediating variable in PT. Pos Indonesia Medan Branch. Using a quantitative method with PLS-SEM analysis on 185 customer respondents selected through purposive sampling, data was collected through a structured questionnaire using Google Form. The results showed that service quality had a positive and significant effect on customer satisfaction (β=0.405, p=0.000) and customer loyalty (β=0.524, p=0.000). Brand image has a positive and significant effect on customer satisfaction (β=0.240, p=0.016) and customer loyalty (β=0.302, p=0.002). Technology usage had a positive and significant effect on customer satisfaction (β=0.504, p=0.000) and customer loyalty (β=0.294, p=0.008). Customer satisfaction was proven to have a positive and significant effect on customer loyalty (β=0.289, p=0.009). Customer satisfaction was able to mediate the influence of service quality (β=0.117, p=0.014), brand image (β=0.112, p=0.019), and technology usage (β=0.146, p=0.025) on customer loyalty. The research model explains 79% of variance in customer loyalty. These findings confirm the importance of a holistic marketing management strategy in the delivery service industry, especially in improving service quality, strengthening brand image, optimizing the use of digital technology, and building customer satisfaction to create long-term loyalty.